2008
DOI: 10.1097/brs.0b013e318178872a
|View full text |Cite
|
Sign up to set email alerts
|

Operative Treatment of Adolescent Idiopathic Scoliosis With Posterior Pedicle Screw-Only Constructs

Abstract: This is the largest (N = 114), consecutive series of North American patients with AIS treated with pedicle screws having a minimum of 3-year follow-up. The average curve correction was 68% for the main thoracic, 50% for the proximal thoracic, and 66% for the thoracolumbar/lumbar curve at final follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
2
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(102 citation statements)
references
References 42 publications
7
82
2
11
Order By: Relevance
“…Hybrid constructs with sub-laminar bands may not offer the same amount of coronal correction than all-screw constructs, however, this difference will not lead to inferior sagittal reciprocal changes. This consideration supports other reports questioning the necessity to obtain a perfect coronal correction to the detriment of sagittal alignment [10,19].…”
Section: Reciprocal Sagittal Interactions and Correlationssupporting
confidence: 90%
See 1 more Smart Citation
“…Hybrid constructs with sub-laminar bands may not offer the same amount of coronal correction than all-screw constructs, however, this difference will not lead to inferior sagittal reciprocal changes. This consideration supports other reports questioning the necessity to obtain a perfect coronal correction to the detriment of sagittal alignment [10,19].…”
Section: Reciprocal Sagittal Interactions and Correlationssupporting
confidence: 90%
“…When applied, the rod-derotation maneuvers can lead to an improvement of the thoracic kyphosis with an average gain reported to be 5°by Suk et al [8], but this can also lead to coronal hypercorrection of the deformity with trunk inclination and shoulder asymmetry [18,19]. Results from this study confirm the ability of hybrid constructs using sub-laminar bands and clamps to maintain TK for normokyphotic patients, and to restore a satisfactory TK for hypokyphotic patients, by applying a posterior traction force on the spine toward pre-bent rods, with an average gain of 6.5°at last follow-up.…”
Section: Hybrid Constructs and Kyphosis Correctionmentioning
confidence: 99%
“…There was also a statistically significant correlation in four of the six coronal balance parameters measured. A recent study of 114 patients with AIS demonstrated maintenance of main curve correction and TL/LC correction from the immediate postoperative films to the 3-year followup radiographs [13]. Therefore, if the intraoperative film strongly correlates with the immediate postoperative film, which it did in our study, the surgeon can get an appreciation of the ultimate correction of the deformity.…”
Section: Discussionsupporting
confidence: 61%
“…Pedicle screws offer three-column fixation and reportedly provide curve correction, maintenance of correction, lower pseudarthrosis rates, fewer implant failures, and fewer postoperative bracing requirements than conventional hook and wire constructs [7,9,16,22]. Additionally, the safety of pedicle screws has been well documented with several large series of patients with AIS undergoing correction with minimal neurologic or visceral complications [13,23,24]. Kim et al [5] reported no neurologic or vascular complications with the placement of over 3000 thoracic pedicle screws.…”
Section: Introductionmentioning
confidence: 99%
“…Thoracic pedicle screws instrumentation, without a direct vertebral derotation, has been found to enhance a loss of sagittal profile (from 8.4°to 12°) by several studies investigating the treatment of AIS [13,23,27,28,32]. In the study of Fu et al [14], at 2-years follow-up, thoracic kyphosis resulted less of the preoperative value (14.5 ± 6.5 vs. 15.8 ± 10.7) in patients treated with screws, in contrast with increased kyphosis obtained at follow-up with hooks construct.…”
Section: Discussionmentioning
confidence: 99%